THE EFFECT OF SELECTION AND TRAINING ON EMPLOYEE PERFORMANCE IN. TRANS RETAIL INDONESIA (CARREFOUR CITRA GARDEN PADANG BULAN) - Rosinta Romauli Situmeang; Rumiris Melvani Tampubolon; Mayang Pebri Yanti; Dosniati Karina (Asian Journal of Innovation and Entrepreneurship, 2019)
ABSTRACT             Employee performance is a level of employee success in carrying out their duties. There are some factors affecting employee performance; some of which are selection and training. Selection is an action to select employees who have the potential to fill positions needed by the company in the hope of making a positive contribution. Training is an activity compiled by the management that aims to improve the skills and abilities of employees to produce high performance so that the goals of the company are achieved. Employee performance can decrease due to a weak selection process and inappropriate training programs. PT. Trans Retail Indonesia (Carrefour) is an international supermarket group that provides daily basic needs. The research method uses a quantitative approach, the type of research used is quantitative descriptive. Data collection is done by interviews, questionnaires and documentation studies. Analysis of the data used is multiple linear regression. The population used is all employees totaling 127 people. Determination of the sample in the study using the Slovin formula is 96 people, while for testing the validity taken 30 respondents outside the study sample. The results showed that simultaneous and partial selection and training had a positive and significant effect on employee performance with a determinant coefficient of 0.742 or 74.2%, while the remaining 25.8% was influenced by other independent variables not examined. The conclusion of the study is that simultaneous and partial selection and training have a significant effect on employee performance at PT. Trans Retail Indonesia.